High-intensity interval training with robot-assisted gait therapy vs. treadmill gait therapy in chronic stroke: a randomized controlled trial - Jiae Kim; Jungwha Do; Cho Rong Bae; Young Hoon Mo; Ji Hye Kim; Dae Yul Kim (Journal of NeuroEngineering and Rehabilitation)
Abstract Objective Stroke is a leading cause of long-term disability, significantly impacting patients’ mobility and quality of life. Robot-assisted gait therapy (RAGT) and high-intensity interval training (HIIT) have individually shown potential in improving gait function in chronic stroke patients. This study investigated the potential effectiveness of combining high-intensity interval training (HIIT) with robot-assisted gait therapy (RAGT) to enhance gait, balance, and lower limb function in patients with chronic stroke. Methods A randomized controlled trial was conducted with 48 patients with chronic stroke, of whom 44 patients (91.7%) completed the study. Participants were randomly assigned to a control group (treadmill-based gait therapy) or an intervention group (RAGT with HIIT using an end-effector robot). Both groups trained for 30 min, three times weekly, over 8 weeks. HIIT alternated between moderate and high intensities. Outcomes included the 10-meter walk test (10MWT), Functional Ambulation Category (FAC), Berg Balance Scale (BBS), Fugl-Meyer Assessment– Lower Extremity (FMA-LE), VO₂max, Modified Barthel Index (MBI), and lean body mass. Results Between-group comparisons showed significant improvements in the intervention group in 10MWT (p < 0.001, d = 1.2), FAC (p = 0.009), BBS (p = 0.015), 2MWT (p = 0.005), and FMA-LE (p < 0.001) scores. Additionally, the intervention group demonstrated enhanced 2MWT (p < 0.001) and VO₂max (p = 0.005) within group; however, lean body mass within-group changes were minor in both groups. The superior outcomes in the intervention group highlight the potential combined benefits of combining HIIT with RAGT for intensive, repetitive, and task-specific training. Conclusion HIIT integrated with RAGT may be an effective approach for improving the gait and functional outcomes of patients with chronic stroke. This novel combination shows promise for enhancing rehabilitation strategies, with potential implications for optimizing functional recovery and quality of life. Trial registration The study was registered with the Clinical Research Information Service (KCT0007659).